Vegetarian Diets and Skeletal Integrity: Mechanisms, Risks, and Future Perspectives - Łapiński, Maciej; Zimnoch-Włodarczyk, Aleksandra; Zinko, Oksana; Napierała, Michał; Ciecierska, Kinga; Wasilkowska, Krystyna; Łatkowska, Sylwia (Quality in Sport, 2026)
Background. Osteoporosis affects over 200 million people worldwide. While vegetarian diets reduce risks of cardiovascular diseases, they raise concerns regarding the intake of nutrients key to skeletal homeostasis, such as vitamin B12 and calcium. Aim. This review analyzes the impact of vegetarian diets on osteoporosis risk and bone physiology. Material and methods. We synthesize current knowledge on nutrient deficiencies, the gut microbiota-bone axis, and biochemical markers including IGF-1 and homocysteine. Results. Vegetarians, especially vegans, exhibit lower bone mineral density and higher fracture risk compared to omnivores. The paper discusses mechanisms such as reduced bioavailable calcium and protein intake, downregulation of the IGF-1 axis, and hyperhomocysteinemia driven by vitamin B12 deficiency. Additionally, we address the potential immunomodulatory role of the gut microbiome. Conclusions. We conclude that plant-based diets are associated with compromised skeletal integrity if not properly balanced. Careful nutritional planning and targeted supplementation are essential to optimize these dietary models for fracture prevention.